High-Efficiency Mushroom Spawn Production Innovation in Mushroom-Producing Communities of Uttaradit Province and Nan Province, Thailand - Kamonkunanon, Siwat; Thanompongchart, Patipat; Chutchaidej, Eakruthai; Wittanalai, Suttida; Rangsisuttaporn, Keowalee; Mueangtoom, Kitti; Thongsiri, Sittinan (Area Based Development Research Journal, 2026)
Background: Mushroom cultivation is an important livelihood activity in northern Thailand, particularly in community-based production systems that supply fresh mushrooms to local and regional markets. In Uttaradit and Nan provinces, fourteen farms in Uttaradit and ten farms in Nan producing Bhutanese oyster mushrooms, oyster mushrooms, and wood ear mushrooms faced persistent production challenges. These included high contamination rates of Trichoderma fungi (5–9%), low yields of less than 250 grams per mushroom block, and elevated production costs. The root causes were identified as inadequate sterilization procedures, poor contamination control during spawn inoculation, and reliance on traditional substrate formulations for mushroom blocks that were not optimized for local environmental conditions. These constraints limited productivity, reduced income stability, and increased losses from contaminated mushroom blocks. Objectives: This study aimed to develop and implement a high-efficiency mushroom block production system that reduces fungal contamination, increases yield, lowers production costs, and strengthens economic, social, and environmental sustainability in mushroom-producing communities. The project also sought to enhance farmers’ technical capacity through participatory knowledge transfer and to demonstrate scalable area-based innovation aligned with local resources and the sufficiency economy philosophy. Methodology: The intervention followed a participatory, multi-stage approach. First, the project fostered awareness and shared understanding through study visits, researcher–farmer knowledge exchange, and systematic knowledge management. These activities culminated in the development of a high-efficiency mushroom block production manual covering four critical stages: (1) mushroom block formulation, (2) sterilization processes, (3) spawn inoculation, and (4) incubation and fruiting management. Second, structured training and on-site learning were conducted, combining theoretical instruction with hands-on mushroom block production and direct technology transfer. Farmers were encouraged to adapt high-efficiency production techniques to their local contexts rather than applying a rigid, standardized model. Third, production procedures were improved through individualized coaching and repeated practice. Farmers in selected subdistricts applied refined sterilization, inoculation, and substrate management methods. Microbiological quality was monitored by measuring yeast and mold contamination, heavy metal residues, and Trichoderma infection rates in mushroom blocks. Results and Findings: The improved production system yielded significant technical and economic gains. High-efficiency mushroom blocks showed yeast and mold contamination levels of 8.6 × 10³ cfu/g, within acceptable safety thresholds (<10.0 × 10³ cfu/g), with no detectable lead or cadmium residues. The Trichoderma contamination rate declined dramatically from 5.8% to 0.1%, representing a 98.5% reduction. Across seven subdistricts, farmers collectively produced 1,248,000 mushroom blocks per year. Improvements in spawn inoculation practices reduced spawn usage per farm and lowered overall production costs by 21.4%. Average mushroom yield increased from 224.8 grams per block to 327.1–342.3 grams per block, corresponding to a 45.5–50.4% increase and an overall productivity gain of approximately 47.5%. These gains translated directly into improved incomes. Farmers earned an additional 45,504–164,592 THB per year (1,516.80 - 5,486.4 USD/Year) from reduced losses and higher yields. Cost savings from reduced spawn usage amounted to 6,000–18,000 THB per year per farm (200 - 600 USD/Year/Farm). Income from increased production rose by 45.3–52.3%, equivalent to 106,995–123,375 THB annually (3,566.50 - 4,112.50 USD/Year). Total net income gains ranged from 158,499 to 305,967 THB per year (5,283.30 - 10,198.90 USD/Year). Outcome, Impacts and Sustainability: The new mushroom fruiting management system cut the amount of working capital needed by up to four times. For example, farmers producing 10,000 blocks could stagger purchases in four cycles of 2,500 blocks, reducing initial capital requirements from 80,000 THB to 20,000 THB (2,666.67 - 666.67 USD) while maintaining continuous monthly income from staggered harvests. Socially, mushroom producers in Uttaradit established a cooperative network to exchange knowledge and jointly procure production materials, reducing input costs and strengthening collective capacity. Increased production also generated local employment, including seasonal jobs for students during school holidays. The innovation focused on making the best use of agricultural waste products that are available in the area, like rice straw, sawdust, rice husk, and other by-products. This approach reduced production costs, improved mushroom quality, and mitigated environmental problems associated with agricultural waste burning.